Managing fast- vs. slow-growth genotypes to optimize quality and yield grades - Schalles, R.R.; Zoellner, K.O.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fast-growth genotype steers placed on a high energy ration a month after weaning were compared to a slow-growth genotype on a growing ration for 155 days, followed by a finishing ration for 62 days. The fast-growth genotype produced heavier, higher quality carcasses in less time than the slow-growth genotype, with similar energy conversion. Using contemporary prices. the fast-growth genotype cattle broke even, and the slow-growth genotype lost $124 per head.
Keywords: Beef; Genotypes; Quality grades; Yield grades